Pemanfaatan Learning Management System (LMS) Berbasis Moodle dalam Pembelajaran Sejarah Pada Kelas X SMK Negeri 3 Magelang - Unik Widayati; Nina Witasari (Indonesian Journal of History Education, 2023)
The purpose of this study is to know the use of LMS Moodle in history study and to know of the obstacles encountered by teachers and trainees in making use of the LMS Moodle. The study uses a qualitative approach with case study strategies. Data collection techniques of observation, interview, and document review. The data collected will then be processed to inference. Research shows that during learning done from home 1) 1) history study with an LMS Moodle is done well. The planning, implementation and evaluations of the history teacher have been systematic. The casting of learning with the LMS Moodle was presensi, matter waiver, and evaluation by taking an formative question. During the online study the history teacher has made good use of, but in doing so has not been fully effective. 2) the challenges teachers experience are the making of attractive materials, the media selection to explain the material, the teachers cannot control the learning activities, and the activation of the learners. The performance of learning is inadequate because of age factors, and learners' accessibility is still lacking, and the class's organization is irregular. The challenge for a learner is the often defective LMS Moodle, an unstable Internet network, a lack of understanding of matter, and a usually full cell phone memory.